Chrysis pseudobrevitarsis Linsenmaier 1951 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
55. Chrysis pseudobrevitarsis Linsenmaier, 1951 Chrysis ignita var. pseudobrevitarsis Linsenmaier 1951: 79. Lectotype ♀ (designated by Linsenmaier 1959: 158); Switzerland: Wallis (NMLS) (examined). Hellén 1952: 180. Chrysis pseudobrevitarsis : Valkeila 1962: 64, Erlandsson 1971: 88, Tumšs 1976: 22, Silfverberg 1981: 61, Vikberg 1986b: 68, Hedström 1989: 154, Nilsson 1991: 82, Soon 2004: 23, 46, Hallin 2009: 10, Johansson 2009, Allearter.dk 2010, Johansson 2010: 118, Orlovskytė et al. 2010: 151, Paukkunen 2010: 538, Smissen 2010d: 393, Johansson 2011: 35, Sjödin 2011, Soon & Saarma 2011: 15, Franzén et al. 2012: 27, Hallin 2012, Ranta 2012: 33, Rosa & Soon 2012, Dyntaxa 2013, Soon et al. 2014: 312–313. Chrysis mediadentata [part.]: Söderman & Vikberg 2003: 45, Material examined. Denmark. B : Almindingen, 17.VI.1964, 1 ♂; NEZ : Tisvilde Hegn, 25.VI.1975, 1 ♀ (Lomholdt). Norway: VAY: Farsund, Kviljo, 4.VII–4.VIII.2008, 1 ♀ (F. Ødegaard). Russian Fennoscandia (total 31 exx.): Ik : Terijoki [= Zelenogorsk]; Äyräpää [= Baryshevo]; Ka : Antrea [= Kamennogorsk]; Jääski [= Lesogorskiy]; Seiskari [= Ostrov Seskar]; Viipuri [= Vyborg]; Kl : Kurkijoki; Sortavala. Distribution. Denmark, Estonia, Finland, Latvia, Lithuania, Norway, Sweden, Russian Fennoscandia.—Transpalearctic: from West Europe to Mongolia (Linsenmaier 1997). Remarks. The species is known from all the Nordic and Baltic countries, but it is usually uncommon and found in low numbers. The northernmost records are from northern Sweden. In Finland it has declined and has been classified as near threatened (Paukkunen 2010). Soon (2004: 46) reported C. pseudobrevitarsis from Norway and Denmark, but later the record from Norway proved to be erroneous. However, one specimen was recently found from southern Norway (Farsund) and the determination was confirmed by DNA barcoding. Records from Denmark are based on two specimens in ZMUC, which were collected from Bornholm and Zealand (see data above). According to mitochondrial DNA studies, the species is divided into two genetically distinct lineages, both of which have been found from the Nordic and Baltic countries (Soon et al. 2014). The other lineage is closer to C. brevitarsis , making C. pseudobrevitarsis paraphyletic, and therefore the lineages could represent different species. The morphological differences and nomenclature of these two lineages remain to be determined. : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on pages 39-40, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Linsenmaier, W. (1951) Die europaischen Chrysididen (Hymenoptera). Versuch einer naturlichen Ordnung mit Diagnosen. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 24, 1 - 110.", "Linsenmaier, W. (1959) Revision der Familie Chrysididae (Hymenoptera) mit besonderer Brucksichtigung der europaischen Spezies. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 32, 1 - 232.", "Hellen, W. (1952) Meeting report: Chrysis brevidens, C. ignita var. impressa, var. angustula, var. aurifera, var. mediater, var. sublongula, var. longula, var. pseudobrevitarsis and ssp. longula new to Finland. Notulae Entomologicae, 32, 180.", "Valkeila, E. (1962) Eraiden lounaissuomalaisten luonnonhistoriallisten maakuntien (V, U, St ja EH) myrkkypistiaiset (Hymenoptera, Aculeata). Lounais-Hameen Luonto, 13, 63 - 73.", "Erlandsson, S. (1971) Catalogus Insectorum Sueciae XIX. Hymenoptera: Aculeata. Entomologisk Tidskrift, 22, 87 - 94.", "Tumss, V. (1976) Materiali Latvijas PSR dzelejplevsparnu (Hymenoptera, Aculeata) faunai. Zoologijas muzeja raksti, 14, 11 - 26.", "Silfverberg, H. (1981) Additions to the Finnish insect fauna during the years 1976 - 1980. Notulae Entomolgicae, 61, 45 - 61.", "Vikberg, V. (1986 b) A checklist of aculeate Hymenoptera of Finland (Hymenoptera, Apocrita Aculeata). Notulae Entomologicae, 66, 65 - 85.", "Hedstrom, L. (1989) Svenska insektfynd - rapport 5. Entomologisk Tidskrift, 110, 149 - 155.", "Nilsson, G. E. (1991) The wasp and bee fauna of the Rido archipelago in Lake Malaren, Sweden (Hymenoptera, Aculeata). Entomologisk Tidskrift, 112, 79 - 92.", "Soon, V. (2004) Eesti kuldherilased (Hymenoptera, Apocrita, Chrysididae). Master's thesis, University of Tartu. 81 pp. Available from: http: // dspace. utlib. ee / dspace / bitstream / handle / 10062 / 1236 / Soon. pdf; jsessionid = 6617 B 92 C 3 E 468623 BC 1 5 CAC 1 E 8 B 95 C 67? sequence = 5 (accessed 1 November 2013)", "Hallin, G. (2009) Gaddsteklar fran Blekinge 1984 - 2007. Sammanstallning av gjorda fynd. Lansstyrelsen i Blekinge lan, Rapport nr 2009: 8, 46 pp.", "Johansson, N. (2009) Skyddsvarda insekter i Ostra Smalands skogsbygder - Jonkopings lan. Lansstyrelsen i Jonkopings lan, Meddelande nr. 2009: 04, 85 + 26 pp.", "Johansson, N. (2010) Solitara gaddsteklar (Hymenoptera: Aculeata) pa tre torrangsartade lokaler i Ovre Emadalen. Entomologisk Tidskrift, 131, 113 - 130.", "Orlovskyte, S., Budriene, A. & Budrys, E. (2010) Check-list of cuckoo-wasps (Hymenoptera: Chrysididae) of Lithuania. New and rare for Lithuania insect species, 22, 141 - 156.", "Paukkunen, J. (2010) Stinging wasps. In: Rassi, P., Hyvarinen, E., Juslen, A. & Mannerkoski, I. (Eds.), The 2010 Red List of Finnish Species. Finnish Ministry of Environment & Finnish Environment Institute, Helsinki, pp. 529 - 544.", "Smissen, J. van der (2010 d) Beitrag zur Stechimmenfauna Schwedens (Hymenoptera Aculeata). Verhandlungen des Vereins fur Naturwissenschaftliche Heimatforschung zu Hamburg e. V., 43, 389 - 398.", "Johansson, N. (2011) Brandinsekter pa Drags udde. Uppfoljning av naturvardsbranningen 2006. Lansstyrelsen i Jonkopings lan, Meddelande 2011: 03, 36 pp.", "Sjodin, E. (2011) Inventering av gaddsteklar pa Angso, Ridon och Aggaron i Vastmanlands lan. Mangfalden i hagmarker fore restaurering och i byggnader med vasstak. Lansstyrelsen i Vastmanlands lan, Rapport nr 2011: 22, 81 + 20 pp.", "Soon, V. & Saarma, U. (2011) Mitochondrial phylogeny of the Chrysis ignita (Hymenoptera: Chrysididae) species group based on simultaneous Bayesian alignment and phylogeny reconstruction. Molecular Phylogenetics and Evolution, 60, 13 - 20. http: // dx. doi. org / 10.1016 / j. ympev. 2011.04.005", "Franzen, M., Molander, M., Noren, L. & Nilsson, L. A. (2012) Forandringar av gaddstekelfaunan pa Kullaberg i Skane. Entomologisk Tidskrift, 133, 1 - 27.", "Hallin, G. (2012) Gaddsteklar i Orebro lan - 60 ars eget samlande och en sammanstallning av befintlig kunskap. Lansstyrelsen i Orebro lan, Publ. Nr 2012: 39, 73 pp.", "Ranta, Y. (2012) Palkaneen kultapistiaiset (Hymenoptera, Chrysididae). Diamina, 21, 30 - 35.", "Rosa, P. & Soon, V. (2012) Fauna Europaea: Chrysididae. In: Mitroiu, M. - D. (Ed.), Fauna Europaea: Hymenoptera, version 2. 5. Available from http: // www. faunaeur. org (accessed 1 November 2013)", "Dyntaxa (2013) Svensk Taxonomisk Databas - Swedish Taxonomic Database (version 1.1.5059.20729). Available from: http: / / www. dyntaxa. se / (accessed 1 November 2013)", "Soon, V., Budrys, E., Orlovskyte, S., Paukkunen, J., Odegaard, F., Ljubomirov, T. & Saarma, U. (2014) Testing the validity of Northern European species in the Chrysis ignita species group (Hymenoptera: Chrysididae) with DNA Barcoding. Zootaxa, 3786 (3), 301 - 330. http: // dx. doi. org / 10.11646 / zootaxa. 3786.3.4", "Soderman, G. & Vikberg, V. (2003 [\" 2002 \"]) Suomen myrkkypistiaisten luettelo ja levinneisyys. Sahlbergia, 7, 41 - 66.", "Linsenmaier, W. (1997) Die Goldwespen der Schweiz. Veroffentlichungen aus dem Natur-Museum Luzern, 9, 1 - 139."]}